Tradisi Penyalinan Al-Qur'an Kuno Sumenep - Hakim, Abdul (Lajnah Pentashihan Mushaf Al-Qur'an, 2016)
Ancient Qur'an is one of the cultural heritages of Islam in Indonesia. It is the result of human interaction with the natural surroundings and at the same time is the unity of some elements of local cultural. Some things revealed in this paper are the elements attached to the copying of an ancient manuscript of the Qur'an, among others are the tradition of the deposit of the instrument, the names of the copyists, the manufacture of paper, ink and binding, as well as the tradition of ornamentation. This study found that ancient Qur'an of the Sumenep was produced from the local cultural roots. Sumenep is known to have the names of the copyist of the Qur'an from the Muslim scholar/clergy to the sultan. The need for ink, paper and binding are also available in the area. It is only the purchase of European paper that must pass through the Dutch government. Decorative Qur'an of Sumenep has in common with the ornaments of buildings and ancient objects that exist in Sumenep. The composition of the ornaments is bright in color with a large pattern, not detail. Something typical in the tradition of the Qur'an in this area is the tradition of Qur'anic storage in small mosque (langgar). Sumenep is a scriptorium of the manuscripts, and the presence of its ancient Qur'an completes remains Islamic objects in this area.